Glaucoma Characteristics and Influencing Factors during the COVID-19 Pandemic in the Huizhou Region - Huilan Zhou; Rui Liao; Dongxuan Zhang; Wei Wang; Shuifeng Deng (Journal of Ophthalmology)
Objective. Glaucoma in individuals who tested positive for the coronavirus disease 2019 (COVID-19) during the pandemic outbreak has not been comprehensively studied. Therefore, this study aimed to analyze the characteristics and risk factors of glaucoma during the COVID-19 pandemic in Huizhou. Methods. Retrospective data from outpatients with glaucoma at the Huizhou Hospital Affiliated with Guangzhou Medical University and Longmen County People’s Hospital were collected during two periods: the COVID-19 pandemic period (Phase A: December 1, 2022, to January 19, 2023) and the prevention and control period (Phase B: December 1, 2021, to January 19, 2022). The demographic characteristics of the outpatients during both phases were compared. The characteristics of glaucoma in patients with COVID-19 during Phase A were examined. Multivariate logistic regression analysis was used to identify factors influencing the development of acute angle-closure glaucoma (AACG) in Phase A patients. Results. The proportion of patients with glaucoma was significantly higher during Phase A than during Phase B at both hospitals. No statistically significant differences were observed between patients with glaucoma during Phases A and B for age, sex, and region. A high COVID-19-positive rate was associated with old age, females, AACG, newly diagnosed glaucoma, and binocular involvement during phase A. Females testing positive for COVID-19, glaucoma that started after testing positive for COVID-19, and a history of medication use were associated with a higher proportion of AACG in phase A. Multivariable logistic regression analysis identified testing positive for COVID-19 as an independent potential risk factor for developing AACG. Conclusion. In summary, during the COVID-19 pandemic in Huizhou, patients with COVID-19 were primarily affected by AACG, especially females, older individuals, and those with binocular involvement. Testing positive for COVID-19 increases the risk of developing AACG.